Influenza vaccination trend and related factors among patients with diabetes in Korea: Analysis using a nationwide database - Lee, Dong-Hwa; Yang, Bumhee; Gu, Seonhye; Kim, Eung-Gook; Kim, Youlim; Kang, Hyung Koo; Choe, Yeong Hun; Jeon, Hyun Jeong; Park, Seungyong; Lee, Hyun (Frontiers in Endocrinology, 2023)
Background Subjects with diabetes are at higher risk of serious influenza-related complications. We aimed to investigate the yearly trend of influenza vaccination and factors associated with being unvaccinated for influenza in subjects with diabetes using a nationwide observational study performed within the recent decade. Methods Among 105,732 subjects from the Korea National Health and Nutrition Examination Survey between 2007 and 2019, 8,632 with diabetes were included. We investigated the yearly trend of influenza vaccination and factors associated with being unvaccinated for influenza. Results During the study period, the prevalence of influenza vaccination in subjects with diabetes showed a tendency to increase every year, reaching almost 60% in 2019, which was higher than the rate in subjects without diabetes. Younger age (adjusted hazard ratio (aHR) [95% CI] 11.29 [8.63–14.75] for < 50 years; 6.16 [5.21–7.29] for 50–65 years), male (aHR 1.67 [1.52–1.87]), current smoker (aHR 1.31 [1.00–1.72], lower-income status (aHR 1.46 [1.17, 1.84]), and high education level (aHR 1.30 [1.01–1.67]) were associated with being unvaccinated. Also, a poorer glycemic control with HbA1c ≥ 9% was found to be correlated with unvaccinated status (aHR 1.48 [1.15–1.90]). Conclusion The influenza vaccination rate is still unsatisfactory in subjects with diabetes. Young age, males, low-income level, high education level, and poor glycemic control were associated with unvaccinated status. Considering the risk-benefits of influenza vaccination in patients with diabetes, physicians should make an effort to increase vaccination rates, especially in low vaccination rate groups.